Genetic estimates and genome-wide association studies of antibody response in Tanzanian dairy cattle - Hernandez-Castro, Luis E.; Cook, Elizabeth Anne Jessie; Matika, Oswald; Mengele, Isaac Joseph; Motto, Shabani Kiyabo; Bwatota, Shedrack Festo; Zirra-Shallangwa, Bibiana; Pong-Wong, Ricardo; Prendergast, James; Mrode, Raphael; Toye, Philip G.; Komwihangilo, Daniel Mushumbusi; et al. (Frontiers in Genetics, 2025)
Identifying the genetic determinants of host defence against infectious pathogens is central to enhancing disease resilience and therapeutic efficacy in livestock. Here, we investigated immune response heritability to important infectious diseases affecting smallholder dairy cattle using variance component analysis. We also conducted genome-wide association studies (GWAS) to identify genetic variants that may help understand the underlying biology of these health traits. By assessing 668,911 single-nucleotide polymorphisms (SNPs) genotyped in 2,045 crossbred cattle sampled from six regions of Tanzania, we identified high levels of interregional admixture and European introgression, which may increase infectious disease susceptibility relative to indigenous breeds. Heritability estimates were low to moderate, ranging from 0.03 (SE ± 0.06) to 0.44 (SE ± 0.07), depending on the health trait. GWAS results revealed several loci associated with seropositivity to the viral diseases Rift Valley fever and bovine viral diarrhoea, the protozoan parasites Neospora caninum and Toxoplasma gondii, and the bacterial pathogens Brucella sp, Leptospira hardjo, and Coxiella burnetii. The identified quantitative trait loci mapped to genes involved in immune defence, tumour suppression, neurological processes, and cell exocytosis. We propose that our results provide a basis for future understanding of the cellular pathways contributing to general and taxon-specific infection responses, and for advancing selective breeding and therapeutic target design.